Factors Contributing to Sphenoid Sinus Volume and Its Relation to Isolated Fungal Sphenoid Sinusitis - Jasmine Pei Ying Kho; Chae-Seo Rhee (Sumatera Medical Journal, 2026)
Background: Isolated Sphenoid Sinus disease is an uncommon entity, with fungal sinusitis being identified as its most common cause. Objective: We investigate factors affecting sphenoid sinus volume (SSV), its pneumatization type, aeration path to the SS ostium, and its relation to isolated fungal sphenoid sinusitis (IFSS). Methods: A total of 43patients with a mean age of 66.6years, histopathologically diagnosed with IFSS, were included in this study. Demographics recorded were age and gender, parameters affecting sinus volume, obstruction of the pathway to the SS ostium, and types of SS pneumatization. The SSV of the pathological and normal sides of the patients was compared. Parameters affecting the incidence of IFSS were evaluated. Results: Presence of lateral recess pneumatization (LRP) and post-sellar type of SS pneumatization significantly increases SSV(p<0.05). There is no significant correlation between SSV and the incidence of IFSS (p=0.815). Obstruction of the airway path to the SS ostium and post-sellar type of SS pneumatization significantly increases the incidence of IFSS (OR = 21.021, p = 0.014; OR =13.59, p=0.02). Conclusion: SSV increases in the presence of LRP, sellar, and post-sellar type of pneumatization. Incidence of IFSS is independent of SS volume. Post-sellar type of SS pneumatization and an obstructed path to the SS ostium increase incidence of IFSS.